Boosting oxygen evolution reaction activity by tailoring MOF-derived hierarchical Co–Ni alloy nanoparticles encapsulated in nitrogen-doped carbon frameworks. Issue 18 (15th March 2021) - Liu, Xiaobin; Zhao, Xudong; Fan, Li-Zhen
Abstract : The hierarchical Co2 Ni@NC nanoparticles realize fast mass transfer for the oxygen evolution reaction (OER). The synergistic effect between Co and Ni can effectively adjust the binding energy tending to an optimal value, further improving the energetics for the OER. Abstract : The growing demand for sustainable energy has led to in-depth research on hydrogen production from electrolyzed water, where the development of electrocatalysts is a top priority. We here report a controllable strategy for preparing the cobalt–nickel alloy nanoparticles encapsulated in nitrogen-doped porous carbon by annealing a bimetal–organic framework. The delicately tailored hierarchical Co2 Ni@NC nanoparticles effectively realize abundant synergistic active sites and fast mass transfer for the oxygen evolution reaction (OER). Remarkably, the optimized Co2 Ni@NC exhibits a small overpotential of 310 mV to achieve a current density of 10 mA cm −2 and an excellent long-term stability in alkaline electrolyte. Furthermore, the underlying synergistic effect mechanism of the Co–Ni model has been pioneeringly elucidated by density functional theory calculations.